Non-directed, carbonate-mediated C–H activation and aerobic C–H oxygenation with Cp*Ir catalysts. Issue 24 (16th March 2016) - Kerr, M. E.; Ahmed, I.; Gunay, A.; Venditto, N. J.; Zhu, F.; Ison, E. A.; Emmert, M. H.
Abstract : Carbonate additives enhance the activity of [Cp*Ir(H2 O)3 ](OTf)2 for non-directed C–H activations and the aerobic C–H oxygenation of alkyl arenes. Abstract : The effect of oxidatively stable L- and X-type additives on the activity of Cp*Ir catalyst precursors in the C–H activation of arenes has been studied. Turnover numbers for C–H activation of up to 65 can thus be achieved, as determined by H/D exchange in MeOH-D4 . In particular, carbonate additives are found to enhance the C–H activation reactivity of Cp*Ir(H2 O)3 (OTf)2 (1 ) more significantly than L-type ligands investigated in this study. Based on these studies, Cp*Ir/carbonate systems are developed that catalyze the aerobic Csp 3 –H oxygenation of alkyl arenes, employing air as oxidant.